Hygrothermal effects on the translaminar fracture toughness of a highly toughened aerospace CFRP: Experimental characterisation and model prediction. (November 2021) - Yu, B.; Katafiasz, T.J.; Nguyen, S.; Allegri, G.; Finlayson, J.; Greenhalgh, E.S.; Pinho, S.T.; Pimenta, S.
Abstract: The translaminar fracture toughness and its dependence on the environmental condition are key considerations in designing aerospace-grade composites with a high damage tolerance to severe service conditions in terms of temperature and moisture. The present work characterises and models the hygrothermal effects on the translaminar fracture toughness of an interlaminar toughened aerospace carbon/epoxy composite under six environmental conditions: −55 °C, 23 °C, and 90 °C, for both 'dry' (i.e. moisture free) and 'wet' (fully moisture-saturated) specimens. Cross-ply compact-tension experiments show that the translaminar fracture toughness increases with the rise of temperature for both dry and wet conditions with the latter exhibiting a much greater increase. A model to predict the effect of moisture and temperature on the translaminar fracture toughness is here proposed and developed. This approach yields good agreement with experimental results, and it allows an improved understanding of the complex synergistic effects of interfacial properties on the overall translaminar toughening mechanisms.